ROOT PROBLEM AND CONFLICT RESOLUTION OF FISHERIES IN SEA WATERS OF SOUTH KALIMANTAN - R usmilyansari (JOURNAL OF COASTAL DEVELOPMENT, 2012)
Conflict of  fisheries (capture fisheries cases  of purse seine) in the sea waters of Kotabaru South Kalimantan, require serious attention. The government has made ​​some efforts to overcome it but not yet effective. Therefore it is important to know more deeply whether conflict resolution is already addressing the root of the problem. The study was conducted with a qualitative approach. The primary data collected through in depth interviews with key informants, while the secondary data obtained from literature studies, relevant agencies and newspaper clippings. Based on the analysis results that: the root causes of conflict based on the source of relationship issues, structural problems and value differences and conflicts based on the typology of conflict of jurisdiction, internal allocation and management mechanism. The resolution of conflict using negotiation and facilitation techniques. Conflict resolution is done is still not addressing the root of the problem so that the escalation of conflicts of fishing last long. Conflict resolution needs to be done effectively by involving stakeholders and increasing their participation in creating the sustainability of capture fisheries.